Diaphragm paper, preparation method thereof and application of diaphragm paper in alkaline battery
By using water-absorbing nanofibers and inorganic porous fillers in alkaline battery separator paper, and combining the coating technology of hydrophilic glue, the shortcomings in storage stability and resistance to external impact are solved, and the separator paper with high adsorption ability and mechanical strength are achieved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202411901189.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
While improving shielding and mechanical strength, existing alkaline battery separator papers are difficult to maintain long-term storage stability and resistance to external impact, and are easily pierced by zinc dendrites.
A slurry containing water-absorbing nanofibers and inorganic porous fillers is used to form a separator paper with high adsorption ability and mechanical strength through the coating of hydrophilic glue solution and the control of a constant temperature and humidity environment.
The high liquid adsorption and storage capacity of diaphragm paper is achieved, which enhances its mechanical strength and shielding, reduces the risk of zinc dendrites penetration, and improves the storage stability and service life of the battery.
Smart Images

Figure CN119686165A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of alkaline battery separators, and in particular to a separator paper and a preparation method thereof and an application thereof in alkaline batteries. Background Art
[0002] Alkaline batteries refer to batteries that use alkaline electrolytes. The most common alkaline batteries are zinc-manganese batteries, which use zinc as the negative electrode, manganese dioxide as the positive electrode, and potassium hydroxide solution as the electrolyte. In order to improve the performance of alkaline batteries, alkaline battery separator paper needs to develop low internal resistance, high shielding properties, and high mechanical strength.
[0003] In the related art, if fine-diameter synthetic fibers and pulped Tencel fibers are used to make diaphragm paper, although the thickness of the diaphragm paper can be reduced and the shielding properties can be improved, the Tencel fibers need to be pulped for a long time to achieve the shielding properties, which is easy to introduce new impurities and shorten the storage time of the battery; if a three-layer structure is used, the upper and lower layers have good liquid absorption, and the middle layer is compounded with fibrillated fibers to make diaphragm paper, although the shielding properties are improved, the preparation method of the diaphragm paper is complicated, and the middle layer has a small quantity and a thin thickness. After long-term storage or external force impact, the shielding properties of the diaphragm paper are difficult to maintain, and zinc dendrites are formed after long-term use and are easy to pierce the diaphragm. Summary of the invention
[0004] In view of the above problems, the present application is proposed. The present application provides a separator paper and a preparation method thereof and an application thereof in alkaline batteries.
[0005] According to one aspect of the present application, a separator paper is provided, wherein the raw materials of the separator paper include:
[0006] Slurry and hydrophilic glue; the slurry includes water-absorbing nanofibers and inorganic porous fillers.
[0007] According to another aspect of the present application, a method for preparing the above-mentioned separator paper is provided, comprising:
[0008] Step 1: adding alkali-resistant synthetic fiber, alkali-resistant cellulose fiber, bonding fiber, water-absorbing nanofiber, defoaming agent and hydrophilic agent into water, and mixing to obtain a slurry intermediate;
[0009] Step 2: adding an inorganic porous filler, a dispersant and a thickener into a slurry intermediate, and mixing to obtain a slurry;
[0010] Step 3: Dewatering the slurry and drying it to obtain base paper;
[0011] Step 4: Coat the surface of the base paper with a hydrophilic adhesive, place the coated base paper in a constant temperature and humidity environment, and dry it to form a hydrophilic adhesive layer to obtain a separator paper.
[0012] In one or more technical solutions provided in the embodiments of the present disclosure, water-absorbing nanofibers and inorganic porous fillers are added to the slurry, wherein the size of the water-absorbing nanofibers is at the nanometer level, which also makes them have a large specific surface area, and their molecular chains are intertwined and entangled with each other, which can form a more complex structure. Therefore, when the water-absorbing nanofibers are used as a component of the diaphragm paper, the contact area with the liquid (for example: electrolyte) can be increased to the greatest extent, and the difficulty of the liquid molecules to escape is increased through their intertwined molecular chains, thereby increasing the diaphragm paper's adsorption capacity and storage capacity for liquids. Not only that, the inorganic porous filler in the embodiments of the present application can further increase the specific surface area of the diaphragm paper to provide more adsorption sites, so that while the nanofibers adsorb liquids, the pores of the inorganic porous filler store liquids, thereby further increasing the diaphragm paper's adsorption capacity and storage capacity for liquids. At the same time, the pulp included in the diaphragm paper in the present application also contains alkali-resistant synthetic fibers, alkali-resistant cellulose fibers, bonding fibers and additives, wherein the above fibers can increase the strength and chemical stability of the diaphragm paper, and firmly fix the inorganic porous filler on the fiber, and the additive can make the above components contact and mix better. On this basis, a hydrophilic glue can be formed on the surface of the base paper made of the above raw materials, which can tightly bond the water-absorbing nanofibers and the inorganic porous filler together, and can reduce the probability of the inorganic porous filler falling off the water-absorbing nanofibers during long-term use. When the diaphragm paper is subjected to external force, this bonding effect can prevent the relative sliding and separation between the fiber and the filler, and enable the water-absorbing nanofibers, inorganic porous fillers and hydrophilic glue to form a barrier structure, thereby not only improving the mechanical strength of the diaphragm paper such as tensile strength and tear resistance, reducing the probability of the diaphragm paper being damaged by impact, resulting in the barrier property of the diaphragm paper being difficult to maintain, but also improving the barrier property of the diaphragm paper. Finally, the coated base paper is placed in a constant temperature and humidity environment and dried to form a hydrophilic adhesive layer to obtain diaphragm paper, which can more accurately control the pore size in the hydrophilic adhesive layer to avoid pores that are too large or too small.
[0013] It can be seen that the diaphragm paper provided in the embodiment of the present application can not only meet the requirements of good liquid adsorption capacity and liquid storage capacity, but also meet the requirements of good mechanical strength and shielding properties.
[0014] According to another aspect of the present application, there is provided a use of the slurry prepared by the above-mentioned diaphragm paper and / or the above-mentioned preparation method of diaphragm paper in alkaline batteries.
[0015] Compared with the prior art, the beneficial effects of the use of the diaphragm paper provided in the present application and / or the slurry prepared by the above-mentioned diaphragm paper preparation method in alkaline batteries are the same as the beneficial effects of the above-mentioned diaphragm paper and its preparation method, which will not be repeated here.
[0016] It is to be understood that both the foregoing general description and the following detailed description are exemplary, and are intended to provide further explanation of the technology as claimed. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] By describing the embodiments of the present application in more detail in conjunction with the accompanying drawings, the above and other purposes, features and advantages of the present application will become more apparent. The accompanying drawings are used to provide a further understanding of the embodiments of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation of the present application. In the accompanying drawings, the same reference numerals generally represent the same components or steps.
[0018] Figure 1 A flow chart of a method for preparing separator paper according to an embodiment of the present application is shown. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present application more obvious, the exemplary embodiments according to the present application will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application, and it should be understood that the present application is not limited to the exemplary embodiments described here.
[0020] Alkaline batteries refer to batteries that use alkaline electrolytes, including zinc-manganese, zinc-mercury, and cadmium-nickel batteries. The most common alkaline battery is the zinc-manganese battery, which uses zinc as the negative electrode, manganese dioxide as the positive electrode, and potassium hydroxide solution as the electrolyte. The alkaline battery separator paper is located between the positive and negative electrodes. The separator paper needs to isolate the positive and negative electrodes to prevent short circuits, and have sufficient porosity to allow ion transmission in the electrolyte; the separator needs to contain alkaline solution to balance the concentration of alkaline solution in the two polar regions during battery discharge; the separator also needs to have a certain mechanical strength to prevent damage to the separator caused by external impact, causing a short circuit in the battery; in order to slow down the formation of zinc dendrites and prevent zinc dendrites from penetrating the large pores in the separator to cause a short circuit, the separator also needs to have a smaller and more evenly distributed pore size. However, if fine-diameter synthetic fibers and pulped Tencel fibers are used to make diaphragm paper, although the thickness consistency and shielding properties of the diaphragm paper can be improved, the Tencel fibers need to be pulped for a long time to achieve shielding properties, which can easily introduce new impurities and shorten the storage time of the battery; if a three-layer structure is used, the upper and lower layers have good liquid absorption, and the middle layer is compounded with fibrillated fibers to make diaphragm paper, although the shielding properties are improved, the preparation method of the diaphragm paper is complicated, and the middle layer has a small quantity and a thin thickness. After long-term storage or external force impact, the shielding properties of the diaphragm paper are difficult to maintain, and zinc dendrites are easily pierced through the diaphragm after long-term use.
[0021] In view of the above problems, the present application provides a diaphragm paper which can not only meet the requirements of good liquid adsorption and liquid storage capacity, but also meet the requirements of good mechanical strength and shielding performance. The raw materials of the diaphragm paper include: pulp and hydrophilic glue; the pulp includes water-absorbing nanofibers and inorganic porous fillers.
[0022] It can be understood that the size of the water-absorbing nanofibers in the embodiments of the present application is at the nanometer level, which also makes it have a large specific surface area, and its molecular chains are intertwined and entangled with each other, which can form a more complex structure. Therefore, when the water-absorbing nanofibers are used as a component of the diaphragm paper, the contact area with the liquid (for example: electrolyte) can be increased to the greatest extent, and the difficulty of the liquid molecules to escape is increased through its intertwined molecular chains, thereby increasing the diaphragm paper's adsorption capacity and storage capacity for liquids. Not only that, the inorganic porous filler in the embodiments of the present application can further increase the specific surface area of the diaphragm paper to provide more adsorption sites, so that while the nanofibers adsorb liquids, the pores of the inorganic porous filler store liquids, thereby further increasing the diaphragm paper's adsorption capacity and storage capacity for liquids. On this basis, the hydrophilic adhesive in the embodiment of the present application can tightly bond the water-absorbing nanofibers and the inorganic porous filler together, which can reduce the probability of the inorganic porous filler falling off the water-absorbing nanofibers during long-term use. When the diaphragm paper is subjected to external force, this bonding effect can prevent the relative sliding and separation between the fibers and the filler, and enable the water-absorbing nanofibers, the inorganic porous filler and the hydrophilic adhesive to form a barrier structure, thereby not only improving the mechanical strength of the diaphragm paper such as tensile strength and tear resistance, reducing the probability of the diaphragm paper being damaged by impact, resulting in the difficulty in maintaining the shielding properties of the diaphragm paper, but also improving the shielding properties of the diaphragm paper.
[0023] It can be seen that the diaphragm paper provided in the embodiment of the present application can not only meet the requirements of good liquid adsorption capacity and liquid storage capacity, but also meet the requirements of good mechanical strength and shielding properties.
[0024] In an optional manner, the hydrophilic glue in the embodiment of the present application is 1 to 8 parts according to the mass fraction in the diaphragm paper; according to the mass fraction in the slurry, the water-absorbing nanofibers are 2 to 10 parts, and the inorganic porous filler is 2 to 8 parts. Within the above-mentioned ratio range, the hydrophilic glue can form sufficient bonding force between the inorganic porous fibers and the inorganic porous filler. This bonding force can prevent the separation of fibers and fillers during the stretching process, not only enabling the diaphragm paper to maintain the integrity of the overall structure when subjected to tensile force, but also enabling the water-absorbing nanofibers, inorganic porous fillers and hydrophilic glue to form a barrier structure, thereby ensuring that the diaphragm paper has good mechanical strength and shielding properties. When the hydrophilic glue is less than 1 part, and the number of other components remains unchanged, the bonding force is insufficient, and the surface pore size is large, and the shielding property of the diaphragm paper is insufficient. When the hydrophilic glue is greater than 8 parts, and the number of other components remains unchanged, it will over-cover the surface of the water-absorbing nanofibers or block their water absorption channels, resulting in too small pore sizes, hindering ion transmission, and increasing internal resistance. At the same time, when the water-absorbent nanofibers are less than 2 parts, the inorganic porous filler is less than 2 parts, and the proportions of other components remain unchanged, it is easy for the liquid adsorption capacity and liquid storage capacity of the diaphragm paper to fall short of expectations; when the water-absorbent nanofibers are greater than 10 parts, the inorganic porous filler is greater than 8 parts, and the proportions of other components remain unchanged, after the diaphragm paper is squeezed or stretched by external force, a large friction force will be generated between the excessive water-absorbent nanofibers and the inorganic porous filler, and local fiber agglomeration is likely to occur, making the structure of the diaphragm paper loose, and the tensile strength and tear strength will be reduced.
[0025] Exemplarily, the water-absorbing nanofibers in the embodiment of the present application include one or more of sodium polyacrylate nanofibers, chitosan-sodium polyacrylate nanofibers and sodium carboxymethyl cellulose nanofibers, wherein the molecular chains of the nanofibers contain a large number of carboxyl groups, which can form hydrogen bonds with water molecules. When in contact with the electrolyte, this nanofiber can quickly absorb and lock a large amount of electrolyte, thereby ensuring that the diaphragm paper always maintains good wettability in the electrolyte environment, which is beneficial to the conduction of ions in the electrolyte. Not only that, the chemical bonds in the chemical structure of the nanofibers can resist the erosion of chemical substances in the electrolyte, thereby maintaining the stable performance of the diaphragm paper, improving its chemical stability, and thus extending the service life of the diaphragm paper. In addition, the inorganic porous filler in the embodiment of the present application includes one or more of calcium carbonate, hydroxyapatite and zirconium oxide. Compared with organic porous fillers, the above-mentioned inorganic porous fillers can increase the specific surface area of the diaphragm paper, ensure that no chemical reaction occurs in the system below 90°C, which is far above the operating temperature, which is beneficial to improve its chemical stability, thereby extending the service life of the diaphragm paper. In addition, the raw material is cheap and readily available, which is conducive to the industrial large-scale production of separator paper.
[0026] Exemplarily, the length of the water-absorbing nanofibers in the embodiment of the present application is 500 μm to 1000 μm. Within this reference range, the water-absorbing nanofibers can form an effective entanglement strength to share the external force together, which is beneficial to reduce the probability of damage to the diaphragm paper after being subjected to external force, thereby improving the tensile strength of the diaphragm paper. When the length of the water-absorbing nanofibers is less than 500 μm, the mechanical strength of the prepared diaphragm paper does not meet expectations. When the length of the water-absorbing nanofibers is greater than 500 μm, the risk of breakage of the water-absorbing nanofibers is increased. Preferably, when the length of the water-absorbing nanofibers is 750 μm to 900 μm, the degree of entanglement between the fibers is high, which is conducive to forming a more regular and compact network structure. When subjected to tensile force, this structure can more effectively transmit and disperse stress. At this time, the electrolyte can be absorbed and conducted more quickly along these more regular fiber networks, thereby improving the liquid absorption efficiency of the diaphragm paper.
[0027] Exemplarily, the diameter of the water-absorbing nanofibers in the embodiment of the present application is 100nm to 900nm. Within this range, if the diameter of the water-absorbing nanofibers is close to 100nm, the pore size of the diaphragm paper is relatively small, and if the diameter of the water-absorbing nanofibers is close to 900nm, the pore size of the diaphragm paper is relatively large. Therefore, the pore size of the diaphragm paper can be accurately controlled. When the diameter of the water-absorbing nanofibers is less than 100nm, the pore size of the diaphragm paper is too small, which is not conducive to ion transmission and increases the internal resistance of the diaphragm paper; when the diameter of the water-absorbing nanofibers is greater than 900nm, the pore size of the diaphragm paper is too large, increasing the probability of being penetrated by zinc dendrites. Preferably, when the diameter of the water-absorbing nanofibers is 500nm to 700nm, the pore size can be more accurately controlled to form a more moderate pore size.
[0028] For example, the particle size of the inorganic porous filler in the embodiment of the present application is 5 to 20 μm. Within this range, the inorganic porous fillers and the fillers and fibers support each other, thereby improving the mechanical strength of the separator paper and preventing excessive deformation of the separator paper. The specific surface area of the inorganic porous filler in the embodiment of the present application is 100 m 2 / g~500m 2 / g, which can provide a large number of adsorption sites, thereby improving the liquid adsorption capacity of the separator paper.
[0029] In an optional manner, the pore size of the diaphragm paper surface in the embodiment of the present application is 2μm to 11μm, and the electrolyte can enter the diaphragm paper through these pores to fully infiltrate it. Its smaller pore size can reduce the probability of short circuit caused by zinc dendrites penetrating due to excessive pore size. This good wettability can ensure that the diaphragm paper maintains good contact with the electrolyte throughout the working process, thereby maintaining stable electrochemical performance, and improving the uniformity of zinc deposition, reducing zinc dendrites caused by high-concentration polarization, and reducing the probability of the diaphragm paper being damaged by zinc dendrites.
[0030] In an optional manner, the raw materials of the hydrophilic glue in the embodiment of the present application include modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane; according to the mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 2 to 15 parts, the N,N-dimethylformamide is 75 to 90 parts, and the polyether-modified siloxane is 2 to 10 parts. Among them, the modified polyvinyl alcohol plays a key role in bonding in the hydrophilic glue. When its mass fraction is 2 to 15 parts, it can provide good bonding force for the diaphragm paper. It can interact with water-absorbing nanofibers and inorganic porous fillers to bind them tightly together. When the content is in this range, it will not cause insufficient bonding force due to too little content, nor will it block the pore size due to too much content, affecting battery performance. For example, in the preparation process of diaphragm paper, it can ensure that the fibers and fillers still maintain a stable structure after drying or curing, preventing them from falling off or shifting during use. The N,N-dimethylformamide in the embodiment of the present application can dissolve modified polyvinyl alcohol and polyether-modified siloxane, so that they are evenly mixed together. When it is within the above parameter range, it can ensure that the hydrophilic glue has good fluidity, which is convenient for forming a hydrophilic glue layer on the surface of the diaphragm paper. The main function of the polyether-modified siloxane in the embodiment of the present application is to slow down the replacement of water and N,N-dimethylformamide in a constant temperature and humidity environment, thereby controlling the size of the pore size. When it is within the above parameter range, it can form a smaller and more evenly distributed pore size on the surface of the diaphragm paper. When the diaphragm paper is in contact with the electrolyte, the hydrophilic glue layer can further increase the adsorption and storage capacity of the diaphragm paper for the liquid, and the smaller pore size on the surface can increase the shielding property of the diaphragm.
[0031] In an optional manner, the slurry in the embodiment of the present application also includes alkali-resistant synthetic fibers, alkali-resistant cellulose fibers, bonding fibers and additives. According to the mass fraction in the slurry, the present application also limits the alkali-resistant synthetic fibers to 20 to 60 parts, the alkali-resistant cellulose fibers to 5 to 30 parts, the bonding fibers to 20 to 40 parts, and the additives to 0.05 to 0.17 parts, and the additives include one or more of defoamers, hydrophilic agents, dispersants and thickeners. Among them, the alkali-resistant synthetic fibers in the embodiment of the present application include one or more of ultrafine vinylon fibers and ultrafine polyolefin fibers; the alkali-resistant cellulose fibers in the embodiment of the present application can be one or more of mercerized pulp and dissolving pulp. The defoamer in the embodiment of the present application includes one or more of silicone defoamers and polyether defoamers. The hydrophilic agent in the embodiment of the present application includes one or more of sodium stearate, sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium bromide. The dispersant in the embodiment of the present application includes one or more of LBD-1 dispersant, sodium lignin sulfonate and R-160 dispersant. The thickener in the embodiment of the present application includes one or more of hydroxyethyl cellulose and modified starch.
[0032] Within the above parameter range, the alkali-resistant synthetic fiber can not only significantly enhance the mechanical properties of the diaphragm paper, but also enable the diaphragm paper to maintain good performance in an electrolyte environment containing alkaline components, thereby improving its chemical stability. The large amount of hydroxyl groups contained in the alkali-resistant cellulose fiber in the embodiment of the present application can form hydrogen bonds with water molecules in the electrolyte, thereby improving the liquid absorption performance of the diaphragm paper, enabling the diaphragm paper to better maintain a wet state, which is beneficial to the conduction of ions in the electrolyte, and also enabling the diaphragm paper to maintain good performance in an electrolyte environment containing alkaline components, thereby improving its chemical stability. The bonding fiber in the embodiment of the present application can further improve the strength of the diaphragm paper, and can make the inorganic porous filler evenly distributed without falling off. Among them, the defoaming agent can prevent the formation of foam or cause the formed foam to break quickly, thereby ensuring that the components of the slurry are evenly mixed and improving the quality of the diaphragm paper. The hydrophilic agent can further enhance the hydrophilicity of the fiber so that the fiber is evenly dispersed in water. The dispersant can generate electrostatic repulsion or steric hindrance effect by adsorbing on the surface of the fiber and filler to prevent them from agglomerating together. This ensures that the microstructure of the separator paper is uniform and improves the consistency of its performance. The thickener can adjust the rheological properties of the slurry according to actual needs so as to prepare a separator paper with expected performance.
[0033] For example, the mass fraction of the defoaming agent is 0.01 to 0.03 parts, the mass fraction of the hydrophilic agent is 0.01 to 0.03 parts, the mass fraction of the dispersant is 0.01 to 0.03 parts, and the mass fraction of the thickener is 0.02 to 0.08 parts.
[0034] Exemplarily, the bonding fibers in the embodiments of the present application include one or more of polyvinyl alcohol fibers, viscose fibers, and sepiolite fibers, wherein the sepiolite fibers have strong adsorption and liquid absorption properties, can better improve the strength of the diaphragm paper, and can make the inorganic porous filler evenly distributed without falling off.
[0035] The embodiment of the present application also provides a method for preparing the above-mentioned diaphragm paper to prepare diaphragm paper with good liquid adsorption capacity, liquid storage capacity, mechanical strength and shielding properties. Figure 1 The flowchart of the method for preparing the separator paper of the embodiment of the present application is shown. Figure 1 As shown, the steps are as follows:
[0036] Step 1: Add alkali-resistant synthetic fiber, alkali-resistant cellulose fiber, bonding fiber, water-absorbing nanofiber, defoaming agent and hydrophilic agent into water, and mix to obtain a slurry intermediate. The total mass percentage of alkali-resistant synthetic fiber, alkali-resistant cellulose fiber, bonding fiber and water-absorbing nanofiber in water is 0.1% to 3%. Within the above parameter range, the fiber can be evenly dispersed in water. The presence of the hydrophilic agent improves the dispersibility of the alkali-resistant synthetic fiber.
[0037] Step 2: Add the inorganic porous filler, dispersant and thickener to the slurry intermediate and mix to obtain the slurry. Under the action of the dispersant and thickener, the dispersibility of the slurry can be improved, the slurry flocculation can be prevented, the rheology of the slurry can be adjusted, the strength and stability of the paper can be improved, and the retention of the inorganic porous filler can be improved.
[0038] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 22g / m 2 ~30g / m 2 It can be seen that the base paper is relatively thin, which is beneficial to reduce the internal resistance of the separator paper and improve the ion transmission capacity. It should be understood that the process of the dehydration treatment and the drying treatment can be adjusted according to the actual situation and is not limited here.
[0039] Step 4: Coat the surface of the base paper with a hydrophilic adhesive, place the coated base paper in a constant temperature and humidity environment, and dry it to form a hydrophilic adhesive layer to obtain a separator paper.
[0040] Exemplarily, in the constant temperature and humidity environment, the temperature of the restricted environment is 20°C to 60°C, and the humidity of the environment is 20%RH to 80%RH. At this time, the adhesive layer liquid can be deliquidized and shrunk, making the final pore size distribution more uniform, and more accurately controlling the pore size in the hydrophilic adhesive layer to avoid the pore size being too large or too small.
[0041] Exemplarily, step 4 further includes: a step of preparing a hydrophilic glue; the step of preparing the hydrophilic glue includes:
[0042] In parts by mass, 1 part of cinnamyl acetate, 0.02 to 0.2 parts of azobisisobutyronitrile and 1 part of methanol are mixed, and the raw materials are stirred under the action of an inert gas, and the first constant temperature condensation reflux is performed, and the dried raw materials are obtained after drying; in parts by mass, 300 to 500 parts of the second part of methanol are added to every 100 parts of the dried product and stirred evenly, and 0.3 to 0.6 parts of sodium hydroxide are added and mixed, and the raw materials are stirred under the action of an inert gas, and the second constant temperature condensation reflux is performed to obtain a hydrophilic glue semi-finished product; the hydrophilic glue semi-finished product is washed with 0.05 to 0.2 parts of acetic acid and 5 to 10 parts of water, and modified polyvinyl alcohol is obtained after drying; the modified polyvinyl alcohol, N, N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. The modified polyvinyl alcohol is insoluble in water, so it can ensure that the pore size can be smoothly adjusted in a constant temperature and humidity environment.
[0043] Exemplarily, the temperature of the first constant temperature condensation reflux in the embodiment of the present application is 40 DEG C ~ 65 DEG C, to ensure that azobisisobutyronitrile can effectively initiate the reaction. In addition, condensation reflux can provide a relatively closed reaction environment, increase the yield and purity of the product. This helps to make the reaction more complete, so that cinnamyl acetate and methanol are fully reacted under the initiation of azobisisobutyronitrile, generate more intermediates, and provide enough reaction amount for subsequent acquisition of drying raw materials. The temperature of the second constant temperature condensation reflux in the embodiment of the present application is 40 DEG C ~ 65 DEG C, and constant temperature condensation reflux can provide a stable environment for these reactions, reduce the interference of external factors (such as temperature changes, reactant concentration fluctuations) on the reaction, and enable the reaction to proceed in the expected direction, generating a hydrophilic glue semi-finished product with stable quality.
[0044] For example, the first constant temperature condensation reflux is accompanied by stirring for 2 to 5 hours, and the second constant temperature condensation reflux is accompanied by stirring for 0.5 to 2 hours to ensure sufficient contact between the reactants.
[0045] The present application also provides an application of the above-mentioned diaphragm paper and / or the preparation method of diaphragm paper in alkaline batteries to ensure the electrical performance of the alkaline batteries and extend the working life of the alkaline batteries.
[0046] In order to verify the effect of the separator paper provided in the examples of the present application, the examples of the present application are demonstrated by way of examples and comparative examples.
[0047] Embodiment 1
[0048] Step 1: According to the mass proportions in the slurry, 60 parts of ultrafine vinylon fiber, 5 parts of mercerized pulp, 15 parts of polyvinyl alcohol fiber, 8 parts of sepiolite fiber, 10 parts of sodium polyacrylate nanofiber, 0.01 parts of silicone defoamer and 0.01 parts of sodium stearate are added into water, and mixed to obtain a slurry intermediate.
[0049] The mass percentage of the total mass of the above fibers in water is 0.1%, the length of the sodium polyacrylate nanofibers is 500 μm, and the diameter of the sodium polyacrylate nanofibers is 100 nm.
[0050] Step 2: According to the mass fraction in the slurry, 2 parts of calcium carbonate with a particle size of 5 μm, 0.01 parts of LBD-1 dispersant and 0.02 parts of hydroxyethyl cellulose are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of calcium carbonate is 100m 2 / g.
[0051] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 22g / m 2 .
[0052] Step 4: In terms of mass fraction, 1 part of cinnamyl acetate, 0.02 parts of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, heated to 40°C while stirring under nitrogen conditions, heated to condense reflux and stirred for 2 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 300 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.3 parts of sodium hydroxide are added, heated to 40°C under nitrogen conditions, stirred at a constant temperature for 0.5 hours, and after stopping heating, 0.05 parts of acetic acid are added for washing, 5 parts of distilled water are added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 15 parts, the N,N-dimethylformamide is 75 parts, and the polyether-modified siloxane is 10 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 20°C and a humidity of 80% RH. After drying, a hydrophilic glue layer is formed to obtain a separator paper. The hydrophilic glue is 1 part by mass in the separator paper.
[0053] Embodiment 2
[0054] Step 1: According to the mass fractions in the slurry, 20 parts of ultrafine polyolefin fibers, 30 parts of dissolving pulp, 30 parts of viscose fibers, 10 parts of sepiolite fibers, 2 parts of chitosan-sodium polyacrylate nanofibers, 0.03 parts of polyether defoamer and 0.03 parts of sodium dodecylbenzene sulfonate are added into water, and mixed to obtain a slurry intermediate.
[0055] The mass percentage of the total mass of the above fibers in water is 0.5%, the length of the sodium polyacrylate nanofiber is 1000 μm, and the diameter of the chitosan-sodium polyacrylate nanofiber is 900 nm.
[0056] Step 2: According to the mass fraction in the slurry, 8 parts of hydroxyapatite with a particle size of 20 μm, 0.03 parts of sodium lignin sulfonate and 0.08 parts of hydroxyethyl cellulose are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of hydroxyapatite is 500m 2 / g.
[0057] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 30g / m 2 .
[0058] Step 4: In terms of mass fraction, 1 part of cinnamyl acetate, 0.2 parts of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, stirred and heated to 65°C under nitrogen conditions, heated to condense reflux and stirred for 5 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 500 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.6 parts of sodium hydroxide are added, heated to 65°C under nitrogen conditions, stirred at a constant temperature for 2 hours, and after stopping heating, 0.2 parts of acetic acid are added for washing, 10 parts of distilled water are added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 2 parts, N,N-dimethylformamide is 90 parts, and the polyether-modified siloxane is 8 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 60°C and a humidity of 20% RH, and dried to form a hydrophilic glue layer to obtain a separator paper. The hydrophilic glue is 5 parts by weight in the separator paper.
[0059] Embodiment 3
[0060] Step 1: According to the mass proportions in the slurry, 50 parts of ultrafine vinylon fiber, 18 parts of dissolving pulp, 15 parts of viscose fiber, 5 parts of sepiolite fiber, 5 parts of sodium carboxymethyl cellulose nanofiber, 0.02 parts of silicone defoamer and 0.02 parts of hexadecyltrimethylammonium bromide are added into water, and mixed to obtain a slurry intermediate.
[0061] The mass percentage of the total mass of the above fibers in water is 2%, the length of the sodium carboxymethyl cellulose nanofiber is 700 μm, and the diameter of the sodium polyacrylate nanofiber is 400 nm.
[0062] Step 2: According to the mass fraction in the slurry, 7 parts of zirconium oxide with a particle size of 10 μm, 0.02 parts of R-60 dispersant and 0.05 parts of modified starch are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of zirconium oxide is 300 m 2 / g.
[0063] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 25g / m 2 .
[0064] Step 4: In terms of mass fraction, 1 part of cinnamyl acetate, 0.1 part of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, stirred and heated to 60°C under nitrogen conditions, heated to condense reflux and stirred for 3 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 400 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.5 parts of sodium hydroxide are added, heated to 60°C under nitrogen conditions, stirred at a constant temperature for 1 hour, and after stopping heating, 0.1 parts of acetic acid are added for washing, distilled water is added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 10 parts, the N,N-dimethylformamide is 88 parts, and the polyether-modified siloxane is 2 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 40°C and a humidity of 60% RH, and dried to form a hydrophilic glue layer to obtain a separator paper. The hydrophilic glue is 8 parts by weight in the separator paper.
[0065] Embodiment 4
[0066] Step 1: According to the mass proportions in the slurry, 60 parts of ultrafine vinylon fiber, 5 parts of mercerized pulp, 15 parts of polyvinyl alcohol fiber, 8 parts of sepiolite fiber, 10 parts of sodium polyacrylate nanofiber, 0.01 parts of silicone defoamer and 0.01 parts of sodium stearate are added into water, and mixed to obtain a slurry intermediate.
[0067] The mass percentage of the total mass of the above fibers in water is 0.1%, the length of the sodium polyacrylate nanofibers is 750 μm, and the diameter of the sodium polyacrylate nanofibers is 500 nm.
[0068] Step 2: According to the mass fraction in the slurry, 2 parts of calcium carbonate with a particle size of 5 μm, 0.01 parts of LBD-1 dispersant and 0.02 parts of hydroxyethyl cellulose are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of calcium carbonate is 100m 2 / g.
[0069] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 22g / m 2 .
[0070] Step 4: In terms of mass fraction, 1 part of cinnamyl acetate, 0.02 parts of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, heated to 40°C while stirring under nitrogen conditions, heated to condense reflux and stirred for 2 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 300 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.3 parts of sodium hydroxide are added, heated to 40°C under nitrogen conditions, stirred at a constant temperature for 0.5 hours, and after stopping heating, 0.05 parts of acetic acid are added for washing, 5 parts of distilled water are added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 15 parts, the N,N-dimethylformamide is 75 parts, and the polyether-modified siloxane is 10 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 20°C and a humidity of 80% RH. After drying, a hydrophilic glue layer is formed to obtain a separator paper. The hydrophilic glue is 1 part by mass in the separator paper.
[0071] Embodiment 5
[0072] Step 1: According to the mass proportions in the slurry, 60 parts of ultrafine vinylon fiber, 5 parts of mercerized pulp, 15 parts of polyvinyl alcohol fiber, 8 parts of sepiolite fiber, 10 parts of sodium polyacrylate nanofiber, 0.01 parts of silicone defoamer and 0.01 parts of sodium stearate are added into water, and mixed to obtain a slurry intermediate.
[0073] The mass percentage of the total mass of the above fibers in water is 0.1%, the length of the sodium polyacrylate nanofibers is 800 μm, and the diameter of the sodium polyacrylate nanofibers is 600 nm.
[0074] Step 2: According to the mass fraction in the slurry, 2 parts of calcium carbonate with a particle size of 5 μm, 0.01 parts of LBD-1 dispersant and 0.02 parts of hydroxyethyl cellulose are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of calcium carbonate is 100m 2 / g.
[0075] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 22g / m 2 .
[0076] Step 4: In terms of mass fraction, 1 part of cinnamyl acetate, 0.02 parts of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, heated to 40°C while stirring under nitrogen conditions, heated to condense reflux and stirred for 2 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 300 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.3 parts of sodium hydroxide are added, heated to 40°C under nitrogen conditions, stirred at a constant temperature for 0.5 hours, and after stopping heating, 0.05 parts of acetic acid are added for washing, 5 parts of distilled water are added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 15 parts, the N,N-dimethylformamide is 75 parts, and the polyether-modified siloxane is 10 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 20°C and a humidity of 80% RH. After drying, a hydrophilic glue layer is formed to obtain a separator paper. The hydrophilic glue is 1 part by mass in the separator paper.
[0077] Embodiment 6
[0078] Step 1: According to the mass proportions in the slurry, 60 parts of ultrafine vinylon fiber, 5 parts of mercerized pulp, 15 parts of polyvinyl alcohol fiber, 8 parts of sepiolite fiber, 10 parts of sodium polyacrylate nanofiber, 0.01 parts of silicone defoamer and 0.01 parts of sodium stearate are added into water, and mixed to obtain a slurry intermediate.
[0079] The mass percentage of the total mass of the above fibers in water is 0.1%, the length of the sodium polyacrylate nanofibers is 900 μm, and the diameter of the sodium polyacrylate nanofibers is 700 nm.
[0080] Step 2: According to the mass fraction in the slurry, 2 parts of calcium carbonate with a particle size of 5 μm, 0.01 parts of LBD-1 dispersant and 0.02 parts of hydroxyethyl cellulose are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of calcium carbonate is 100m 2 / g.
[0081] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 22g / m 2 .
[0082] Step 4: In terms of mass fraction, 1 part of cinnamyl acetate, 0.02 parts of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, heated to 40°C while stirring under nitrogen conditions, heated to condense reflux and stirred for 2 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 300 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.3 parts of sodium hydroxide are added, heated to 40°C under nitrogen conditions, stirred at a constant temperature for 0.5 hours, and after stopping heating, 0.05 parts of acetic acid are added for washing, 5 parts of distilled water are added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 15 parts, the N,N-dimethylformamide is 75 parts, and the polyether-modified siloxane is 10 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 20°C and a humidity of 80% RH. After drying, a hydrophilic glue layer is formed to obtain a separator paper. The hydrophilic glue is 1 part by mass in the separator paper.
[0083] Comparative Example 1
[0084] Step 1: According to the mass percentage in the slurry, 40 parts of ultrafine polyolefin fibers, 30 parts of dissolving pulp, 30 parts of polyvinyl alcohol fibers, 0.01 parts of silicone defoaming agent and 0.01 parts of sodium stearate are mixed uniformly in water to obtain a slurry. The mass percentage of the total mass of the above fibers in water is 2%.
[0085] Step 2: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 30g / m 2 .
[0086] Step 3: In terms of mass fraction, 1 part of cinnamyl acetate, 0.2 parts of azobisisobutyronitrile, and 1 part of methanol are stirred evenly, stirred and heated to 65°C under nitrogen conditions, heated to condense reflux and stirred for 5 hours, and then placed in a vacuum oven for drying after stopping heating. In terms of mass fraction, 500 parts of methanol are added to every 100 parts of the dried product and stirred evenly, 0.6 parts of sodium hydroxide are added, heated to 65°C under nitrogen conditions, stirred at a constant temperature for 2 hours, and after stopping heating, 0.2 parts of acetic acid are added for washing, 5 parts of distilled water are added for washing, and vacuum drying is performed to obtain modified polyvinyl alcohol. Subsequently, the modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue. Among them, in terms of mass fraction in the hydrophilic glue, the modified polyvinyl alcohol is 2 parts, N,N-dimethylformamide is 90 parts, and the polyether-modified siloxane is 8 parts. The hydrophilic glue is coated on both sides of the base paper, and the coated base paper is placed in a constant temperature and humidity environment with a temperature of 60°C and a humidity of 20% RH, and dried to form a hydrophilic glue layer to obtain a separator paper. The hydrophilic glue is 1 part by mass in the separator paper.
[0087] Comparative Example 2
[0088] Step 1: According to the mass percentage in the slurry, 20 parts of ultrafine polyolefin fiber, 30 parts of dissolving pulp, 30 parts of viscose fiber, 10 parts of sepiolite fiber, 2 parts of sodium polyacrylate nanofiber, 0.02 parts of silicone defoamer and 0.02 parts of sodium stearate are mixed uniformly in water to obtain a slurry intermediate. The mass percentage of the total mass of the above fibers in water is 0.1%, the length of the sodium polyacrylate nanofiber is 900 μm, and the diameter of the sodium polyacrylate nanofiber is 700 nm.
[0089] Step 2: According to the mass fraction in the slurry, 8 parts of hydroxyapatite with a particle size of 20 μm, 0.02 parts of LBD-1 dispersant and 0.04 parts of hydroxyethyl cellulose are added to the slurry intermediate, and the slurry is obtained after mixing. Among them, the specific surface area of hydroxyapatite is 100 m 2 / g.
[0090] Step 3: Dehydrate the slurry and dry it to obtain the base paper. The weight of the base paper is 30g / m 2 .
[0091] Step 4: Gluing is applied to both sides of the base paper, wherein the glue liquid is a polyvinyl alcohol solution, and after drying, the separator paper is obtained. The glue liquid is 1 part by weight in the separator paper.
[0092] The alkali absorption height, alkali retention rate and tensile strength of the separator paper were tested in accordance with "QB / T 4173-2011 Alkaline Zinc-Manganese Dioxide Battery Separator". The average pore size of the separator paper was measured using a BSD-PB membrane pore size analyzer. The battery separator paper was assembled into LR6 batteries, and the average discharge times of the new batteries were tested in accordance with the discharge conditions of "camera flash" in "T / ZZB 0333-2018 High-capacity, environmentally friendly LR6 / LR03 alkaline zinc-manganese dioxide batteries".
[0093] The following are the performance test results of the diaphragm papers prepared in Examples 1 to 6 and the diaphragm papers prepared in Comparative Examples 1 to 2.
[0094] Table 1
[0095]
[0096] 1. Compared with comparative example 1, water-absorbing nanofibers and inorganic porous fillers are added in examples 1 to 6, so that the diaphragm paper provided in the present application has a high liquid retention rate and good alkalinity absorption. After adding the water-absorbing nanofibers, the pore size of the diaphragm paper is further adjusted, thereby increasing the shielding and zinc dendrite resistance of the diaphragm paper.
[0097] 2. Compared with Examples 1 to 3, Examples 4 to 6 limit the length of the water-absorbing nanofibers to 750 μm to 900 μm and the diameter to 500 nm to 700 nm, thereby effectively improving the alkali absorption height, alkali retention rate and tensile strength.
[0098] 3. Compared with comparative example 2, embodiments 1 to 6 use hydrophilic glue coating, and use polyether modified siloxane and ambient temperature and humidity to adjust the pore size. The coated diaphragm paper homogenizes the circulation of the electrolyte, increases the number of discharges of the battery at high currents, and improves the mechanical strength of the diaphragm paper.
[0099] The above is only a specific implementation of the present application. Obviously, various modifications and combinations can be made without departing from the spirit and scope of the present application. Accordingly, this specification and the drawings are only exemplary illustrations of the present application as defined by the attached claims, and are deemed to have covered any and all modifications, changes, combinations or equivalents within the scope of the present application. Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is intended to include these changes and variations. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be covered within the scope of protection of the present application. Therefore, the scope of protection of the present application shall be based on the scope of protection of the claims.
[0100] It should also be noted that in the device and method of the present application, each component or each step can be decomposed and / or recombined. Such decomposition and / or recombination should be regarded as equivalent solutions of the present application.
[0101] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use the present application. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of the present application. Therefore, the present application is not intended to be limited to the aspects shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
[0102] The above description has been given for the purpose of illustration and description. In addition, this description is not intended to limit the embodiments of the present application to the forms disclosed herein. Although multiple example aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, changes, additions and sub-combinations thereof.
Claims
1. A separator paper, characterized in that: The raw materials of the diaphragm paper include: pulp and hydrophilic glue; the pulp includes water-absorbing nanofibers and inorganic porous fillers.
2. The separator paper according to claim 1, characterized in that: According to the mass fraction in the separator paper, the hydrophilic glue is 1 to 8 parts; according to the mass fraction in the slurry, the water-absorbing nanofiber is 2 to 10 parts, and the inorganic porous filler is 2 to 8 parts.
3. The separator paper according to claim 2, characterized in that: The water-absorbing nanofibers include one or more of sodium polyacrylate nanofibers, chitosan-sodium polyacrylate nanofibers and sodium carboxymethyl cellulose nanofibers, and the inorganic porous filler includes one or more of calcium carbonate, hydroxyapatite and zirconium oxide.
4. The separator paper according to claim 3, characterized in that: The length of the water-absorbing nanofiber is 500 μm to 1000 μm, and the diameter of the water-absorbing nanofiber is 100 nm to 900 nm.
5. The separator paper according to claim 3, characterized in that: The particle size of the inorganic porous filler is 5 to 20 μm, and the specific surface area of the inorganic porous filler is 100 m 2 / g~500m 2 / g.
6. The separator paper according to claim 1, characterized in that: The pore size on the surface of the separator paper is 2 μm to 11 μm.
7. The separator paper according to claim 1, characterized in that: The raw materials of the hydrophilic glue include modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane; according to the mass parts in the hydrophilic glue, the modified polyvinyl alcohol is 2 to 15 parts, the N,N-dimethylformamide is 75 to 90 parts, and the polyether-modified siloxane is 2 to 10 parts.
8. The separator paper according to any one of claims 1 to 7, characterized in that: The slurry also includes alkali-resistant synthetic fibers, alkali-resistant cellulose fibers, bonding fibers and additives; calculated by weight in the slurry, the alkali-resistant synthetic fibers are 20 to 60 parts, the alkali-resistant cellulose fibers are 5 to 30 parts, the bonding fibers are 20 to 40 parts, and the additives are 0.05 to 0.17 parts, and the additives include one or more of a defoaming agent, a hydrophilic agent, a dispersant and a thickener.
9. The separator paper according to claim 8, characterized in that: The bonding fibers include one or more of polyvinyl alcohol fibers, viscose fibers, and sepiolite fibers.
10. A method for preparing the diaphragm paper according to any one of claims 1 to 9, characterized in that: The preparation method comprises: Step 1: adding alkali-resistant synthetic fiber, alkali-resistant cellulose fiber, bonding fiber, water-absorbing nanofiber, defoaming agent and hydrophilic agent into water, and mixing to obtain a slurry intermediate; Step 2: adding an inorganic porous filler, a dispersant and a thickener into a slurry intermediate, and mixing to obtain a slurry; Step 3: Dehydrating the slurry and drying it to obtain base paper; Step 4: coating the hydrophilic adhesive on the surface of the base paper, placing the coated base paper in a constant temperature and humidity environment, and drying to form a hydrophilic adhesive layer to obtain a separator paper.
11. The method for preparing separator paper according to claim 10, characterized in that: The weight of the base paper is 22 g / m 2 ~30g / m 2 .
12. The method for preparing separator paper according to claim 10, characterized in that: In step 4, the temperature of the environment is 20° C. to 60° C., and the humidity of the environment is 20% RH to 80% RH.
13. The method for preparing separator paper according to claim 10, characterized in that: The step 4 further comprises: a step of preparing the glue solution; the step of preparing the glue solution comprises: After mixing cinnamyl acetate, azobisisobutyronitrile and the first portion of methanol, the mixture is subjected to a first constant temperature condensation reflux under the action of an inert gas, and then dried to obtain a dried raw material; After mixing the dried raw material, the second portion of methanol and sodium hydroxide, a second constant temperature condensation reflux is performed under the action of an inert gas to obtain a hydrophilic glue semi-finished product; washing the semi-finished hydrophilic glue product and drying it to obtain modified polyvinyl alcohol; Modified polyvinyl alcohol, N,N-dimethylformamide and polyether-modified siloxane are mixed to obtain a hydrophilic glue.
14. The method for preparing separator paper according to claim 13, characterized in that: The temperatures of the first constant temperature condensation reflux and the second constant temperature condensation reflux are both 40°C to 65°C.
15. Use of a preparation method comprising the diaphragm paper according to any one of claims 1 to 9 and / or the diaphragm paper according to any one of claims 10 to 14 in alkaline batteries.